De Geer moraine internal architecture based on sedimentological and geophysical investigations and implications for ice-marginal reconstructions - Rivers, Gwyneth E.; Storrar, Robert D.; Ojala, Antti E. K.; Mäkinen, Joni; Holmroos, Camilla; Holmes, Naomi (WILEY, 2025)
De Geer moraines (DGMs) may act as valuable ice margin indicators; however, to date, their variable mode of formation has presented challenges for this utility. Morphometric investigations provide useful insights into formation processes, which can be developed using sedimentological and geophysical methods. Here we present sedimentological and ground penetrating radar (GPR) data of DGMs located in southwest Finland. Individual lithofacies were identified and interpreted using sediment architectural elements. These were correlated with neighbouring GPR radargrams and extrapolated across the wider study area. Generally, internal architecture presents a multi-phase structure with lower units representing subglacial traction till and ice margin infill deposits, truncated by a larger prominent push unit, which is then successively deformed via the overriding of active ice. Significantly, there are notable differences between proximal and distal structures, with proximal sides characterized by silts, clays, and diamicton with laminae, stratification and thrust planes, and distal sides characterized by poorly consolidated diamicton and proglacial water current reworkings. Internal architecture of both prominent and intermediate ridges is very similar, reflecting similar formation processes, however, slight differences also reflect inter-seasonal variations. Based on our findings, we present an integrated conceptual model for the genesis of DGMs whereby inter-seasonal ridge forming processes occur within a sub-aqueous ice-marginal environment. Our model highlights that DGMs can be subcategorized as: (i) sediment deposition at an unstable margin during summer calving, and/or (ii) sediment pushing at a stabilized margin during a winter re-advance. We do not find evidence of crevasse filling as a mechanism for DGM formation. We propose a landform assemblage classification whereby 'De Geer terrain' is used to describe series of parallel ridges arranged in a typical washboard-like configuration. This classification identifies all DGMs derived within a sub-aqueous ice-marginal environment, whilst also capturing the equifinal characteristics between individual landforms.